2021
DOI: 10.24875/bmhim.20000295
|View full text |Cite
|
Sign up to set email alerts
|

A pediatric case of Bartonella henselae and Epstein Barr virus disease with bone and hepatosplenic involvement

Abstract: Background: Cat scratch disease (CSD) is an infectious disorder caused by Bartonella henselae. The infection usually presents as local lymphadenopathy, fever, and mild constitutional symptoms. Systemic or severe disease is reported in 5-20% of patients with CSD. We report a case of disseminated CSD with osteomyelitis and hepatosplenic disease and a review of the literature. Case report: A previously healthy 5-year-old male presented with prolonged fever and abdominal pain, followed by low back pain. The serolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…13,14 Several cases of atypical CSD that mimic other diseases have been reported in the literature. Other etiologies include metastatic tumors, 15 Epstein–Barr virus infection, 16 and autoimmune diseases. 17 Kara et al reported a suspected case of CSD neuroretinitis, which was eventually diagnosed as systemic lupus erythematosus based on a positive result for antinuclear antibody.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Several cases of atypical CSD that mimic other diseases have been reported in the literature. Other etiologies include metastatic tumors, 15 Epstein–Barr virus infection, 16 and autoimmune diseases. 17 Kara et al reported a suspected case of CSD neuroretinitis, which was eventually diagnosed as systemic lupus erythematosus based on a positive result for antinuclear antibody.…”
Section: Discussionmentioning
confidence: 99%
“…6,9 In contrast, in hepatosplenic CSD, micro-abscesses are detected in the liver and spleen, as evidenced by imaging techniques, such as ultrasound, computed tomography and magnetic resonance imaging. 16,18 Multiple granulomatous lesions are relatively specific signs, and thus, it would be reasonable to initiate treatment for atypical CSD based these characteristic imaging findings together with a history of contact with cats. 19 It should be noted, however, that these imaging findings may also closely resemble sarcoidosis, candidiasis, and advanced metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to point out that a case of concomitant B henselae and Epstein-Barr virus infection has been described. 8 Even in that case, the B henselae infection may have reactivated Epstein-Barr virus as well as HHV-6 and HHV-7 in the case described by Swink et al 1 Epstein-Barr virus reactivation has been detected in one case 8 serologic testing-IgM, IgG, Epstein-Barr virus nuclear antigen IgG, and heterophile antibodies-as there were no dermatologic manifestations that may be related to Epstein-Barr virus reactivation from latency. 9 In conclusion, a viral or bacterial infection such as Epstein-Barr virus or B henselae may have a transactivating function allowing another (latent) virus such as HHV-6 or HHV-7 to reactivate.…”
mentioning
confidence: 86%
“…in staphylococci; Kim et al, 2014) with the exception of atypical mycobacteria, where macrolides are often the backbone therapy in combination with other active substances (Griffith et al, 2007). Azithromycin has successfully been used as a stepdown oral therapy or in combination with other antibiotics in treatment of osteomyelitis with rare or resistant pathogens like Salmonella typhi (Ayeni and Calver, 2012), Bartonella henselae (Aparicio-Casares et al, 2021), or resistant pneumococci (Riordan et al, 2008), and it may be an option for treatment in combination with rifampicin (Shirtliff et al, 1999;O'Reilly et al, 1992). Although good quality evidence Abbreviations: MIC: minimal inhibitory concentration, qd: once a day, bid: twice a day, tid: three times a day, iv: intravenous, po: per os is still lacking, azithromycin may be a treatment option in select cases.…”
Section: No Source Identifiedmentioning
confidence: 99%